INTERNALISATION OF KEBHINNEKATUNGGALIKAAN AND PANCASILA VALUES: A CASE STUDY at SMP NEGERI 4 AMBON - Wenno, Eldaa Crystle; Tentua, Frando A (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2024)
This research aims to explore the process of internalizing the values of Kebhinnekatunggalikaan and Pancasila at SMP Negeri 4 Ambon, a school with a high ethnic and religious diversity background. Using a qualitative approach with a case study method, the research collected data through observation, in-depth interviews, documentation, and focus group discussions (FGDs). The findings show that SMP Negeri 4 Ambon has successfully integrated these values into the curriculum and various school activities. The interactive approach and collaborative projects applied by teachers proved effective in facilitating the understanding and application of the values of Kebhinnekatunggalikaan and Pancasila among students. Teachers and school staff play a key role as role models and mentors. However, challenges still exist, especially in relation to the different backgrounds of the students, which sometimes give rise to exclusionary attitudes. Nonetheless, this internalization program has improved harmony among students and built a harmonious school climate. The study recommends further development of the character education curriculum, improved teacher training, collaboration with the local community, and adequate resource support for program sustainability. The findings provide valuable insights for the development of character education practices in other schools and education policy in Indonesia.